New dimensions of linguistic inequality: an overview - Bonnin, Juan Eduardo (2013)
Relationships between language and inequality are a constitutive part of contemporary sociolinguistic theory which, despite certain specialized discussions and controversies, has developed a well-established set of theoretical assumptions. Our aim in this paper is to introduce an overview of these as well as to point out some emerging new perspectives on the issue of linguistic inequality. After a short introduction to critical sociolinguistics, I will analyze the shift from ‘diversity discourse’, which can be traced back to the mid-1980s in the USA, towards a new global focus on inequality, which emerged around the end of the 1990s. In the second place, we will describe some theoretical aspects of the concept of ‘linguistic inequality’ following current sociolinguistic bibliography on the matter, with special interest in globalization processes and the relationships of individuals with the state. In the third place, we review recent literature on new dimensions of linguistic inequality, with a special focus on (a) relationships between local and global language varieties; (b) multilingual practices and civil rights; and (c) multilingualism in educational settings. In the final section of this paper, we encourage the continuity of the research on new dimensions of linguistic inequality as a way of empowering linguistic minorities whose access to basic civil rights is impeded by asymmetrical language relationships.